Association between Genetic Polymorphisms of DNA Repair Genes and Chromosomal Damage for 1, 3-Butadiene-Exposed Workers in a Matched Study in China. (3rd August 2015) - Xiang, Menglong; Sun, Lei; Dong, Xiaomei; Yang, Huan; Liu, Wen-bin; Zhou, Niya; Han, Xue; Zhou, Ziyuan; Cui, Zhihong; Liu, Jing-yi; Cao, Jia; Ao, Lin
Abstract : The aim of the study was to examine the association between polymorphisms of DNA repair genes and chromosomal damage of 1, 3-butadiene- (BD-) exposed workers. The study was conducted in 45 pairs of occupationally exposed workers in a BD product workshop and matched control workers in an administrative office and a circulatory water workshop in China. Newly developed biomarkers (micronuclei, MNi; nucleoplasmic bridges, NPBs; nuclear buds, NBUDs) in the cytokinesis-blocked micronucleus (CBMN) cytome assay were adopted to detect chromosomal damage. PCR and PCR-restriction fragment length polymorphism (RFLP) are adopted to analyze polymorphisms of DNA repair genes, such as X-ray repair cross-complementing Group 1 ( XRCC1 ), O6 -methylguanine-DNA methyltransferase ( MGMT ), poly (adenosine diphosphate-ribose) polymerases ( ADPRT ), and apurinic/apyrimidinic endonucleases ( APE1 ). The BD-exposed workers exhibited increased frequencies of MNi and NPBs when compared to subjects in the control group. The results also show that the BD-exposed workers carrying XRCC1 diplotypes TCGA-CCGG (4.25 ± 2.06 ‰ ) (FR = 2.10, 95% CI: 1.03–4.28) and TCGG-TCGA (5.80 ± 3.56 ‰ ) (FR = 2.75, 95% CI: 0.76–2.65) had statistically higher NBUD frequencies than those who carried diplotype TCGG-TCGG (1.89 ± 1.27 ‰ ). Our study suggests that polymorphisms of XRCC1 gene may influence chromosomal damage in BD-exposed workers.